Increased Cytosolic Calcium Contributes to Hydrogen-Rich Water-Promoted Anthocyanin Biosynthesis Under UV-A Irradiation in Radish Sprouts Hypocotyls - Zhang, Xiaoyan; Wei, Junyu; Huang, Yifan; Shen, Wenbiao; Chen, Xin; Lu, Chungui; Su, Nana; Cui, Jin (Frontiers in Plant Science, 2018)
Our previous studies showed that hydrogen-rich water (HRW) promoted the biosynthesis of anthocyanin under UV-A in radish. However, molecular mechanism involved in the regulation of the anthocyanin biosynthesis is still unclear. In this study, the role of calcium (Ca2+) in HRW-promoted anthocyanin biosynthesis in radish sprouts hypocotyls under UV-A was investigated. The results showed that a positive effect of HRW on the content of cytosolic calcium and anthocyanin accumulation, mimicking the effects of induced CaCl2. Exogenous addition of Ca2+ chelator bis (β-aminoethylether)-N,N,N′,N′-tetraacetic acid (EGTA) and inositol 1,4,5-trisphosphate (IP3) synthesis inhibitor neomycin partially reversed the facilitated effect of HRW. The positive effects of HRW on activity of anthocyanin biosynthetic-enzymes (L-phenylalanine ammonia-lyase, PAL; chalcone isomerase, CHI; dihydroflavonol 4-reductase, DFR and UDP glc-flavonoid 3-O-glucosyl transferase, UFGT) were reversed by EGTA and neomycin. Further tests confirmed that the upregulation of anthocyanin biosynthetic related genes induced by HRW was substantially inhibited by calcium antagonists. The possible involvement of CaM in HRW-regulated anthocyanin biosynthesis was also preliminarily investigated in this study. Taken together, our results indicate that IP3-dependent calcium signaling pathway might be involved in HRW-regulated anthocyanin biosynthesis under UV-A irradiation.